Super-easy-to-clean ceramic tile with long-acting antibacterial self-cleaning glaze layer and preparation method thereof

CN122940480APending Publication Date: 2026-10-20HAIOU CHAMPION BUILDING MATERIALS (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611232699.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]然而,釉面在烧成过程中受坯釉排气、釉料收缩、局部析晶和冷却应力等因素影响,表面仍可能存在针孔、浅凹坑、开口细裂或析晶边界凹陷等开口微缺陷,上述开口微缺陷的入口边缘多呈突变状或锐角状,含菌液膜、油污液膜和含水垢离子的水膜流经釉面时,容易在入口边缘处发生挂附和残留,残留液膜进一步携带蛋白质、油污、无机盐和细菌停留在缺陷入口附近,经过反复润湿和干燥后,容易形成难以擦除的局部污渍和菌污残留

Benefits of technology

通过在釉面层中形成低熔封边玻璃相,使其在烧成后段对开口微缺陷入口边缘进行圆钝化处理,减弱入口边缘对菌污液膜的挂附作用,降低污染物在针孔、浅凹坑和开口细裂处的残留。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses an ultra-easy-clean ceramic tile with a long-lasting antibacterial and self-cleaning glaze layer and its preparation method, belonging to the field of ceramic tile preparation. The glaze layer comprises a main glaze glass phase and a low-melting-point sealing glass phase distributed within the main glaze glass phase. The outer surface of the glaze layer has micro-defects communicating with the outside world, and these micro-defects have openings located on the outer surface of the glaze layer. By forming a low-melting-point sealing glass phase in the glaze layer, the entry edges of the micro-defects are rounded and passivated during the later stages of firing, reducing the adhesion of the entry edges to the bacterial and contaminant film and reducing the residue of contaminants in pinholes, shallow pits, and fine cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic tile manufacturing technology, and more specifically, to an ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer and its manufacturing method. Background Technology

[0002] After firing, ceramic tile glazes typically have high density and smoothness, which can meet the requirements of daily decoration, stain prevention and cleaning. For places that are prone to contact with moisture, oil and microorganisms, such as kitchens, bathrooms and hospital corridors, existing products usually improve easy cleaning and antibacterial properties by increasing the smoothness of the glaze, reducing surface energy or adding antibacterial components.

[0003] However, during the firing process, the glaze surface is affected by factors such as venting of the body and glaze, shrinkage of the glaze, local crystallization, and cooling stress. As a result, there may still be micro-defects on the surface, such as pinholes, shallow pits, fine cracks, or recessed crystallization boundaries. The entrance edges of these micro-defects are often abrupt or acute-angled. When bacterial films, oil films, and water films containing scale ions flow through the glaze surface, they are easy to adhere to and remain at the entrance edges. The residual liquid film further carries proteins, oil, inorganic salts, and bacteria and stays near the defect entrance. After repeated wetting and drying, it is easy to form local stains and bacterial residues that are difficult to wipe off.

[0004] Existing technologies mostly improve the overall smoothness of the glaze, surface wettability, or the content of antibacterial components, but do not pay enough attention to the problem of dirt accumulation at the edge of the opening micro-defect. Even if the overall glaze is relatively smooth, the abrupt change at the edge of the opening micro-defect can still become the initial retention site of bacterial and dirt film, affecting the ease of cleaning and antibacterial retention effect of the tile after long-term use. Summary of the Invention

[0005] To address the problems mentioned in the background section, the present invention provides the following technical solution: An ultra-easy-clean ceramic tile with a long-lasting antibacterial and self-cleaning glaze layer and its preparation method, comprising a body and a glaze layer disposed on the surface of the body, wherein the glaze layer comprises a main glaze glass phase and a low-melting-point sealing glass phase distributed in the main glaze glass phase; The outer surface of the glaze layer has micro-defects that communicate with the outside world, and the micro-defects have an opening located on the outer surface of the glaze layer; The low-melting-point sealing glass phase forms a rounded edge sealing phase at at least part of the rim, the rounded edge sealing phase covering the acute angle turning point of the rim, and forming an arc-shaped transition edge at the junction of the micro-defect and the outer surface of the glaze layer. The radius of curvature of the arc-shaped transition edge is greater than the radius of curvature of the acute angle turning position of the opening edge where the rounded edge seal phase is not formed, thereby weakening the contact line pinning of the bacterial contaminant film at the micro-defect opening edge. Furthermore, the micro-defects include at least one of pinholes, microcracks, glaze pits, and crystal boundary depressions; The rim is the entrance edge formed by the intersection of the micro-defect and the outer surface of the glaze layer.

[0006] Furthermore, the rounded edge is continuously or discontinuously distributed along the circumference of the opening edge; The rounded edge covers 40% to 100% of the total circumferential length of the rim.

[0007] Furthermore, the radius of curvature of the arc-shaped transition edge is 1.5 μm to 15 μm; The depth of the rounded edge extending into the micro-defect is 0.5 μm to 8 μm.

[0008] Furthermore, the softening temperature of the low-melting-point sealing glass phase is lower than that of the main glaze glass phase; The difference between the softening temperature of the low-melting-point sealing glass phase and the softening temperature of the main glaze glass phase is 30°C to 160°C.

[0009] Furthermore, the low-melting-point sealing glass phase includes at least one of borosilicate glass phase, zinc borosilicate glass phase, lithium borosilicate glass phase, and sodium calcium borosilicate glass phase.

[0010] Furthermore, the low-melting-point sealing glass phase is formed by firing low-melting-point sealing glass powder; The amount of low-melting-point sealing glass powder added is 0.3% to 8% based on the total mass of the glaze used to prepare the glaze layer; The D50 particle size of the low-melting-point sealing glass powder is 0.5 μm to 10 μm.

[0011] A method for preparing an ultra-easy-clean ceramic tile with a long-lasting antibacterial and self-cleaning glaze layer includes the following steps: Preparation of green body; A glaze layer containing a main glaze and low-melting-point sealing glass powder is applied to the surface of the blank. The green body with the glaze layer applied is fired to form the main glaze glass phase and the low melting point sealing glass powder to form the low melting point sealing glass phase. During the later stages of firing or the initial stages of cooling, the low-melting-point sealing glass phase is kept fluid and enriched at the edges of micro-defects on the outer surface of the glaze layer. After cooling, the low-melting-point sealing glass phase is solidified at the edge of the micro-defect to form a rounded edge sealing phase. The rounded edge sealing phase covers the acute angle turning point of the micro-defect edge and forms an arc-shaped transition edge.

[0012] Furthermore, the softening temperature of the low-melting-point sealing glass powder is 30°C to 160°C lower than the softening temperature of the main glaze glass phase formed by the main glaze. After the main glaze glass phase has basically taken shape, the low melting sealing glass phase is still in a flowable state and undergoes local backflow to the acute angle turning position of the micro-defect edge under the action of surface tension.

[0013] Furthermore, the firing process includes a peak heat preservation section and an edge sealing and forming section; The peak heat preservation section is used to melt the main glaze and form a continuous glaze surface; The temperature of the edge sealing forming section is lower than the temperature of the peak heat preservation section, but higher than the softening temperature of the low melting point edge sealing glass powder. The heat preservation time of the edge sealing forming section is 3 to 30 minutes, so that the low melting edge sealing glass phase preferentially forms a rounded edge sealing phase at the edge of the micro-defect, without requiring complete filling of the internal space of the micro-defect as a necessary condition.

[0014] In summary, the present invention has the following beneficial effects: By forming a low-melting-point sealing glass phase in the glaze layer, the entry edge of the micro-defect is rounded and passivated after firing, which weakens the adhesion of the bacterial and dirt film at the entry edge and reduces the residue of pollutants in pinholes, shallow pits and fine cracks.

[0015] By reducing the initial retention sites of bacterial and dirt films, oil, protein, scale, and bacteria are less likely to form continuous residues at the entrance of micro-defects in the glaze, thereby improving the ease of cleaning and antibacterial retention of the tiles. Attached Figure Description

[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0017] Figure 1 This is a schematic diagram of the overall structure of the ceramic tile of the present invention; Figure 2 This is an enlarged schematic diagram of the edge sealing structure for the opening micro-defect entrance of the present invention; Figure 3 This is a schematic diagram of the preparation method of the present invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1

[0020] The following is in conjunction with the appendix Figure 1-3 The present invention will be described in further detail below.

[0021] Please see Figure 1-3 This invention provides a technical solution: an ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer and its preparation method, such as... Figure 1-3 As shown, it includes a blank body and a glaze layer disposed on the surface of the blank body. The glaze layer includes a main glaze glass phase and a low melting sealing glass phase distributed in the main glaze glass phase. The outer surface of the glaze layer has micro-defects that communicate with the outside world, and the micro-defects have an edge located on the outer surface of the glaze layer; The low-melting-point sealing glass phase forms a rounded edge sealing phase at at least part of the edge, the rounded edge sealing phase covers the acute angle turning position of the edge, and forms an arc-shaped transition edge at the junction of the micro-defect and the outer surface of the glaze layer. The radius of curvature of the arc-shaped transition edge is greater than the radius of curvature of the acute angle turning point of the edge where the rounded edge seal phase has not been formed, which weakens the contact line pinning of the bacterial sludge film at the edge of the micro-defect.

[0022] Micro-defects include at least one of pinholes, microcracks, glaze pits, and crystal boundary depressions; The rim is the entrance edge formed by the intersection of a micro-defect and the outer surface of the glaze layer.

[0023] The rounded edge seal is continuously or intermittently distributed along the circumference of the edge; The rounded edge seal covers 40% to 100% of the total circumferential length of the mouth edge.

[0024] The radius of curvature of the arc-shaped transition edge is 1.5 μm to 15 μm; The extension depth inside the rounded edge facing micro-defect is 0.5 μm to 8 μm.

[0025] In this embodiment: 600mm×600mm ultra-easy-clean glazed ceramic tiles were prepared using porcelain tile blanks as the base. After pressing and molding, the tile blanks were dried, and the moisture content of the blanks after drying was 0.38%. Before glazing, the surface of the blanks was blown to remove dust to avoid floating powder affecting the glaze layer spreading.

[0026] The glaze uses a transparent glossy glaze as the base glaze, which contains feldspar, quartz, kaolin, wollastonite, alumina, and transparent frit. To improve the edge morphology at the entrance of micro-defects in the glaze surface, zinc borosilicate low-melting-point glass powder is added to the base glaze. This low-melting-point glass powder, measured by a laser particle size analyzer, has a D50 particle size of 3.6 μm and a D90 particle size of 7.8 μm; its softening temperature, measured by a high-temperature microscope, is approximately 714℃. The softening temperature of the main glaze glass phase formed after firing the base glaze is approximately 812℃, a difference of approximately 98℃. The amount of low-melting-point glass powder added is 2.6% of the dry basis weight of the glaze.

[0027] A glaze slurry was prepared by ball milling a mixture of base glaze, low-melting-point glass powder, water, sodium carboxymethyl cellulose, and sodium tripolyphosphate. The glaze slurry was tested through a 325-mesh sieve, and the residue was 0.22%, with a specific gravity of 1.75 g / cm³. 3 The flow rate was 39s. The glaze slurry was applied to the surface of the body using a spray glazing method. The wet glaze amount, converted to dry glaze amount, was approximately 486g / m³. 2 After glazing, the body is dried in hot air at 90℃ for 12 minutes. Once the glaze surface is no longer sticky, it enters the firing process.

[0028] The dried brick blanks were then fed into a roller kiln for firing. The firing cycle was 64 minutes, with a maximum firing temperature of 1162℃ and a high-temperature holding time of approximately 10 minutes. After the high-temperature stage, the subsequent temperature zone was controlled at around 890℃, allowing the brick blanks to remain in this zone for about 8 minutes. During this stage, the glaze surface generally stabilized, while the localized glass phase formed by the low-melting-point glass powder still maintained a certain degree of fluidity. Microscopic observation of the fired samples revealed that the low-melting-point glass phase was mainly distributed at the edges of pinholes, shallow pits, and the entrances of localized fine cracks, while no obvious dripping or localized glaze accumulation was observed in the main glaze area.

[0029] After firing and cooling, five brick samples from the same batch were taken. Three observation points were selected in the central and edge areas of each brick sample, and the entrance morphology of glaze opening defects was observed using a scanning electron microscope. In the ordinary transparent glossy glaze sample without the addition of low-melting-point glass powder, the entrance edges of some pinholes and shallow pits showed obvious abrupt changes, with sharp turns visible at the edges. In the sample of this embodiment, a thin glassy transition edge was formed at the entrance edge. This transition edge was continuously or semi-continuously distributed along the defect entrance, transforming the original sharp edge into a gentler curved edge.

[0030] Thirty open defects were cross-sectionally measured using a three-dimensional white-light interferometric profilometer. The radius of curvature of the arc-shaped transition edge at the defect entrance was found to be mainly between 3.9 μm and 6.8 μm, with an average of 5.4 μm; the depth of the glassy transition edge extending into the defect was mainly between 1.6 μm and 3.2 μm, with an average of 2.4 μm. Based on the circumferential length of the defect entrance, the coverage ratio of the low-melting glass phase ranged from 68% to 84%, with an average coverage ratio of 76.5%. From the cross-sectional morphology, a certain amount of concave space remained inside the defects, and the morphological changes at the entrance edge were quite significant.

[0031] To observe the impact of changes at the entrance edge on contamination, brick samples from this embodiment and ordinary glossy glazed bricks without added low-melting-point glass powder were compared. Simulated bacterial contamination containing E. coli suspension, peptone, and a small amount of edible oil was dripped onto the brick sample surface, 50 μL at each test point. After standing at room temperature for 15 min, the samples were rinsed with 0.12 MPa water for 15 s, and then photographed and analyzed under the same lighting conditions. The ordinary glossy glazed sample showed obvious annular residue at the pinholes and shallow pits at the entrance, with the residue concentrated mainly at the opening edge. In this embodiment, the residual liquid film was mainly scattered dots, with significantly reduced continuous residue at the opening edge.

[0032] Statistical analysis of five test areas showed that the residual contamination area of ​​ordinary glossy glaze samples after rinsing accounted for 11.4% to 13.1% of the test area, with an average of 12.2%; while the residual contamination area of ​​the samples in this embodiment accounted for 2.6% to 3.4% of the test area, with an average of 3.0%. After rinsing, the samples were placed at 37°C for 24 hours, followed by surface wiping and sampling. The residual bacterial count of the ordinary glossy glaze samples was 2.4 × 10⁻⁶. 4 CFU / cm 2 Up to 3.1×10 4 CFU / cm 2 The residual bacterial count of the sample in this embodiment was 3.8 × 10⁻⁶. 3 CFU / cm 2 Up to 5.2×10 3 CFU / cm 2 .

[0033] In this embodiment, the glassy transition edge formed by the low-melting-point glass powder in the later stage of firing improves the abrupt edge change at the entrance of the micro-defect. When the bacterial contaminant film passes through the glaze, the number of adhesion points at the defect entrance is reduced, the residual area after rinsing is reduced, and the amount of residual colonies subsequently decreases accordingly.

[0034] Example 2

[0035] like Figure 1-3 As shown, the softening temperature of the low-melting-point sealing glass phase is lower than that of the main glaze glass phase. The difference between the softening temperature of the low-melting-point sealing glass phase and the softening temperature of the main glaze glass phase is 30°C to 160°C.

[0036] The low-melting-point sealing glass phase includes at least one of borosilicate glass phase, zinc borosilicate glass phase, lithium borosilicate glass phase, and sodium calcium borosilicate glass phase.

[0037] The low-melting-point sealing glass phase is formed by firing low-melting-point sealing glass powder; The amount of low-melting-point sealing glass powder added is 0.3% to 8% based on the total mass of the glaze used to prepare the glaze layer; The D50 particle size of the low melting point sealing glass powder is 0.5 μm to 10 μm.

[0038] In this embodiment, under the same green body, the same basic glaze, and the same firing regime, the amount, particle size, and softening temperature of low-melting glass powder were adjusted to observe its influence on the edge morphology of the micro-defect inlet of the glaze surface.

[0039] The base glaze is a transparent glossy glaze. After firing, the softening temperature of the main glaze glass phase, as measured by a high-temperature microscope, is approximately 812℃. Low-melting-point glass powders were selected from zinc borosilicate glass powder and lithium zinc borosilicate glass powder. The low-melting-point glass powders were first melted, water-quenched, dried, and ball-milled, then air-classified to obtain batches with different particle sizes. After each batch of low-melting-point glass powder was added to the base glaze, glaze slurries were prepared under the same ball-milling conditions. The residue on a 325-mesh sieve was controlled between 0.18% and 0.28%, and the specific gravity was controlled at 1.73 g / cm³. 3 Up to 1.76 g / cm 3 The flow rate is controlled between 37s and 42s.

[0040] Table 1. Detection results of low-melting-point glass powder parameters and the edge morphology of the micro-defect inlet.

[0041] Each sample was prepared using 600mm×600mm porcelain tile blanks, and the dry glaze amount was controlled at 470g / m². 2 Up to 500g / m 2 The firing cycle is 64 minutes, with a maximum firing temperature of 1160℃ to 1165℃ and a high-temperature holding time of approximately 10 minutes. After the high-temperature stage, the temperature zone is controlled at around 890℃, and the brick blank is held in this temperature zone for approximately 8 minutes. After firing and cooling, three brick samples are randomly selected from each group of samples. For each brick sample, one observation point is taken from the central area, one from the edge area, and one from the diagonal area. A total of no less than 45 opening defects are observed in each group.

[0042] In sample A1, the amount of low-melting-point glass powder added was relatively low. Glassy transition edges were visible at the edges of some pinholes and shallow pits, but the distribution was not continuous. Sharp local transitions were still visible in the microscopic cross-section, and after rinsing, contaminant easily formed short arc-shaped residues at the uncovered edges. The average coverage ratio of the inlet edges in this group of samples was 42.8%, and the average radius of curvature of the arc-shaped transition edges was 1.9 μm.

[0043] The entry edge finishing of samples A2 and A3 was relatively stable. The low-melting glass phase formed a thin, continuous or semi-continuous transition edge at the entrance of the opening defect, with no obvious flow observed in the main glaze area. In sample A3, the average radius of curvature of the arc-shaped transition edge was 5.4 μm, and the average depth extending into the defect was 2.4 μm. SEM observation showed that the glassy transition edge of this group of samples was mainly located near the entrance edge, and a identifiable recessed space remained inside the defect.

[0044] In sample A4, the coverage ratio of the entrance edge was further improved, and a wider, smoother edge was formed at the entrance of some shallow pits. The surface gloss of this group of samples remained normal, and no localized glaze buildup was visible to the naked eye. The average radius of curvature of the arc transition edge was measured to be 7.2 μm using a three-dimensional white light interferometer, and the degree of abrupt change at the entrance edge was further reduced compared to samples A2 and A3.

[0045] In sample A5, the inlet edge coverage reached 91.6%, and a glassy transition edge could be observed at most pinholes and shallow pits. This group of samples showed a strong smoothing effect on the inlet edge, but slight bright spots appeared at a few observation points, and the uniformity of the glaze gloss was slightly reduced in some areas. Combined with the microscopic observation results, although an excessive amount of low-melting-point glass powder is beneficial to improving the inlet edge coverage, it will have a certain impact on the stability of the glaze appearance.

[0046] Simulated bacterial contamination rinsing tests were conducted on each group of samples. The simulated bacterial contamination solution was prepared by mixing E. coli suspension, peptone aqueous solution, and edible oil. 50 μL was added to each test point, allowed to stand at room temperature for 15 min, and then rinsed with 0.12 MPa water for 15 s. After rinsing, the residual area was statistically analyzed using image analysis software. The average residual contamination area of ​​sample A1 was 6.8%, sample A2 was 4.1%, sample A3 was 3.0%, sample A4 was 2.5%, and sample A5 was 2.3%. Among them, samples A3 and A4 showed a relatively balanced performance in terms of entrance edge finishing, glaze appearance uniformity, and residual contamination area.

[0047] The results of this embodiment show that when the softening temperature of the low-melting-point glass powder is lower than that of the main glaze glass phase, it can retain a certain degree of fluidity in the later stage of firing and form a glassy transition edge at the entrance edge of the opening defect. When the amount of low-melting-point glass powder added is low, the entrance edge coverage is insufficient; when the amount added is high, the entrance edge coverage ratio is increased, but the local appearance stability of the glaze is affected. When the D50 particle size is controlled at around 3μm to 5μm, the low-melting-point glass powder is more uniformly dispersed in the glaze slurry, and the transition structure at the entrance edge is more stable after firing.

[0048] Example 3

[0049] like Figure 1-3 As shown, it includes the following steps: Preparation of green body; A glaze layer containing the main glaze and low-melting-point sealing glass powder is applied to the surface of the blank; The green body with the glaze layer is fired to form the main glaze glass phase and the low melting point sealing glass powder forms the low melting point sealing glass phase. During the later stages of firing or the early stages of cooling, the low-melting-point sealing glass phase is kept fluid and enriched at the edges of micro-defects on the outer surface of the glaze layer. After cooling, the low-melting-point sealing glass phase solidifies at the edge of the micro-defect to form a rounded edge sealing phase. The rounded edge sealing phase covers the acute angle turning point of the micro-defect edge and forms an arc-shaped transition edge.

[0050] The softening temperature of the low-melting-point sealing glass powder is 30°C to 160°C lower than the softening temperature of the glass phase of the main glaze formed by the main glaze. After the main glaze glass phase has basically taken shape, the low melting sealing glass phase is still in a flowable state and undergoes local backflow to the acute angle turning position of the micro-defect edge under the action of surface tension.

[0051] The firing process includes a peak heat preservation section and an edge sealing and forming section; The peak heat preservation section is used to melt the main glaze and form a continuous glaze surface; The temperature of the edge sealing forming section is lower than that of the peak insulation section, but higher than the softening temperature of the low melting point edge sealing glass powder. The heat preservation time of the edge sealing forming section is 3 to 30 minutes, so that the low melting edge sealing glass phase preferentially forms a rounded edge sealing phase at the edge of the micro-defect, rather than requiring complete filling of the internal space of the micro-defect as a necessary condition. In this embodiment, based on the ratio of the basic glaze and low-melting-point glass powder used in Example 1, the firing temperature and dwell time were adjusted to observe the forming state of the inlet edge of the micro-defect. The low-melting-point glass powder used was zinc borosilicate glass powder with a D50 particle size of 3.6 μm and a softening temperature of approximately 714°C. The amount added was 2.6% of the dry basis mass of the glaze. The softening temperature of the main glaze glass phase formed after firing the basic glaze was approximately 812°C.

[0052] All samples used 600mm×600mm porcelain tile blanks, and the dry glaze amount was controlled at 480g / m². 2 Up to 495g / m 2 The specific gravity of the glaze slurry is controlled at 1.74 g / cm³. 3 Up to 1.76 g / cm 3 The flow rate was controlled at 38 to 41 seconds, and the residue on the 325-mesh sieve was controlled at 0.20% to 0.25%. After drying, the brick blanks were fired in a roller kiln with a firing cycle of 63 to 66 minutes and a maximum firing temperature of 1160 to 1164℃. The high-temperature holding time was approximately 10 minutes. After the high-temperature stage, the temperature and residence time of the subsequent temperature zone were adjusted to form samples B1 to B5.

[0053] Table 2. Process parameters after firing and edge forming results of the opening micro-defect inlet.

[0054] The final temperature range of sample B1 was 810℃, close to the temperature range where the main glaze glass phase begins to stabilize. Scanning electron microscopy observation after firing revealed numerous sharp bends at the pinhole and shallow pit entrances, with the low-melting glass phase only showing a dotted distribution at some entrance edges. Three-dimensional white light interferometry profilometry showed that the average coverage ratio of the entrance edges for this group of samples was 31.6%, and the average radius of curvature of the arc-shaped transition edges was 1.4 μm. After rinsing with simulated bacterial contaminants, the contaminant residue remained mainly concentrated at the pinhole and shallow pit entrances.

[0055] The temperature range of sample B2 was increased to 850℃ in the later stage, and the residence time was maintained for 8 minutes. In this group of samples, the continuity of the distribution of the low-melting glass phase at the edge of the opening defect was improved. Some pinhole entry points formed thinner glassy transition edges, and the sharpness of the shallow pit edges was reduced. The average coverage ratio of the entry edge in this group of samples was 58.9%, and the average residual contamination area decreased to 4.9%.

[0056] Sample B3 was fired at a temperature of 890℃ for 8 minutes. After firing, the glaze had a uniform gloss and no visible glaze flow marks. Scanning electron microscopy revealed continuous or semi-continuous glassy transition edges at the entrances of pinholes, shallow pits, and localized fine cracks. Measurements at 30 open defect sections showed an average radius of curvature of 5.4 μm for the arc-shaped transition edges and an average depth of 2.4 μm within the low-melting-point glass phase defects. The average residual contamination area after rinsing with simulated bacterial contaminant was 3.0%, with the residue points mostly scattered.

[0057] The temperature range of sample B4 was increased to 930℃ in the later stage, while the residence time remained at 8 minutes. The average coverage rate of the inlet edge for this group of samples was 88.2%, the average radius of curvature of the arc-shaped transition edge was 8.7 μm, and the edge transition at the entrance of the opening defect was wider. The overall gloss of the glaze remained normal, but the width of the glassy transition edge near the entrance of some shallow pits was excessive. The average residual contamination area was 2.6%, slightly lower than that of sample B3.

[0058] The rear temperature zone of sample B5 was 950℃, and the residence time was extended to 14 minutes. Most of the samples in this group exhibited a glassy transition edge at the entrance edge of open defects, with an average edge coverage rate of 93.8%. Microscopic observation revealed that some low-melting-phase glass-like defects extended deeply into the interior, and a few areas showed slight bright spots. The uniformity of the glaze appearance was slightly worse than that of samples B3 and B4. The average residual contamination area was 2.5%, showing only a small improvement compared to sample B4.

[0059] The simulated bacterial contamination rinsing test was conducted according to the method in Example 1. Five test areas were selected for each sample, and 50 μL of simulated bacterial contamination was added to each area. After standing at room temperature for 15 min, the area was rinsed with 0.12 MPa water for 15 s. After taking pictures, the residual area was counted using image analysis software. The test results showed that when the temperature in the later stage was too low, the coverage of the low-melting glass relative to the entrance edge of the opening defect was insufficient, and the bacterial contamination was easy to remain at the untrimmed entrance edge. After the temperature in the later stage increased, the number of arc-shaped transition edges formed at the entrance edge increased, and the area of ​​contamination residue decreased accordingly. When the temperature and residence time were further increased, the coverage ratio of the entrance edge continued to increase, but the local appearance stability of the glaze began to decrease.

[0060] Based on observations of the inlet edge morphology, residual contamination area, and glaze appearance, when the temperature in the later stage is controlled between 870℃ and 930℃ and the residence time is controlled between 6 min and 12 min, the distribution of the low-melting glass phase at the inlet edge of the micro-defect is relatively stable, and no obvious glaze accumulation or dripping is observed in the main glaze area. Within this temperature range, the main glaze glass phase has tended to stabilize, while the low-melting glass phase can still locally spread at the inlet edge, forming a relatively stable arc-shaped transition structure after firing and cooling.

[0061] Comparative Example 1 This comparative example prepared ordinary transparent glossy glazed ceramic tiles. The body, glazing method, and firing cycle were basically the same as in Example 1. The glaze slurry used transparent glossy glaze as the base glaze material, which contained feldspar, quartz, kaolin, wollastonite, alumina, and transparent frit, but no low-melting glass powder was added.

[0062] After ball milling, the glaze slurry had a residue of 0.24% on a 325-mesh sieve and a specific gravity of 1.74 g / cm³. 3The flow rate was 40 seconds. The glaze was applied to the surface of a 600mm x 600mm porcelain tile using a spray method. The wet glaze amount, converted to dry glaze weight, was approximately 482g / m². 2 After glazing, the brick blanks are dried in hot air at 90℃ for 12 minutes, and then sent to a roller kiln for firing. The firing cycle is 64 minutes, the maximum firing temperature is 1161℃, and the high-temperature holding time is about 10 minutes. After the high-temperature stage, the subsequent temperature zone is cooled according to the conventional cooling curve, without setting a holding section near 890℃.

[0063] After firing and cooling, five brick samples from the same batch were examined for glaze surface observation. Scanning electron microscopy revealed that the glaze surface was generally continuous, with pinholes, shallow pits, and a few fine cracks in localized areas. Some pinholes showed abrupt changes at their entry edges, and sharp bends were observed at the edges of the shallow pits. Cross-sectional measurements of 30 open defects were performed using a three-dimensional white light interferometry profilometer. The radius of curvature at the defect entry edges was mainly distributed between 0.4 μm and 1.1 μm, with an average of 0.7 μm; no continuously distributed glassy transition edge along the circumference of the entry was observed.

[0064] The simulated bacterial contamination rinsing test was conducted according to the method in Example 1. 50 μL of simulated bacterial contamination was added to each test point, and after standing at room temperature for 15 min, it was rinsed with water at a flow rate of 0.12 MPa for 15 s. After rinsing, ring-shaped or short arc-shaped residues were visible at the entrances of pinholes and shallow pits. Statistical analysis of the five test areas showed that the contamination residue area accounted for 11.4% to 13.1% of the test area, with an average of 12.2%. After rinsing, the samples were placed at 37°C for 24 h, and surface samples were taken by wiping. The residual colony count was 2.4 × 10⁻⁶. 4 CFU / cm 2 Up to 3.1×10 4 CFU / cm 2 .

[0065] Comparative Example 2 This comparative example prepared ordinary super easy-clean glazed ceramic tiles using porcelain tile blanks of the same specifications as in Example 1. A transparent glossy glaze was used as the base glaze, and a conventional siloxane-based easy-cleaning additive was added to the base glaze at a rate of 0.35% of the dry weight of the glaze. No low-melting-point glass powder was added to the glaze.

[0066] After ball milling, the glaze slurry had a residue of 0.20% on a 325-mesh sieve and a specific gravity of 1.75 g / cm³. 3 The flow rate is 38 seconds. The glaze is applied to the surface of the brick using a spray method, with a dry glaze weight of approximately 488 g / m². 2After glazing, the brick blanks are dried with hot air at 90℃ for 12 minutes before being fired in a roller kiln. The firing cycle is 65 minutes, the maximum firing temperature is 1160℃, and the high-temperature holding time is about 10 minutes. The post-firing section is cooled according to the production curve of ordinary super easy-clean glaze, and no heat preservation zone is set for the forming of the low-melting glass phase inlet edge.

[0067] After firing and cooling, the sample surface exhibited a relatively uniform gloss, and water droplets spread at a slower rate in the smooth glaze area compared to Comparative Example 1. The surface felt smoother when wiped. Scanning electron microscopy revealed that the smooth glaze area was relatively dense, but abrupt boundaries remained at the entrance edges of pinholes, shallow pits, and localized fine cracks. Three-dimensional white light interferometry was used to measure the cross-sections of 30 opening defects. The radius of curvature at the defect entrance was mainly distributed between 0.6 μm and 1.5 μm, with an average of 1.0 μm. Some opening defects showed signs of glaze leveling improvement around their entrances, but no stable glassy transition edge was formed covering the entrance edge.

[0068] A simulated bacterial contamination rinsing test was conducted according to the method in Example 1. After rinsing, the residue in the smooth glaze area was reduced compared to Comparative Example 1, but obvious discontinuous ring-shaped residues were still present at the edges of pinholes and shallow pits. Statistics from five test areas showed that the contamination residue area accounted for 7.6% to 9.1% of the test area, with an average of 8.4%. After rinsing, the samples were placed at 37°C for 24 hours, and surface samples were taken by wiping. The residual bacterial count was 1.6 × 10⁻⁶. 4 CFU / cm 2 Up to 2.1×10 4 CFU / cm 2 .

[0069] Comparative Example 3 In this comparative example, the same zinc borosilicate low-melting-point glass powder as in Example 1 was added to the base glaze. The low-melting-point glass powder had a D50 particle size of 3.6 μm, a softening temperature of approximately 714 °C, and was added at 2.6% of the dry basis weight of the glaze. The preparation of the body, glaze slurry, glaze application amount, and drying conditions were all the same as in Example 1.

[0070] The glaze slurry was tested through a 325-mesh sieve, and the residue was 0.23%, with a specific gravity of 1.75 g / cm³. 3 The flow rate is 40 seconds. The glaze is applied to the surface of a 600mm x 600mm porcelain tile using a spray method, with a dry glaze weight of approximately 485g / m². 2 After glazing, the brick blanks are dried with hot air at 90℃ for 12 minutes and then sent to a roller kiln for firing. The firing cycle is 64 minutes, the maximum firing temperature is 1162℃, and the high-temperature holding time is about 10 minutes. After the high-temperature stage, the brick blanks are rapidly cooled through the 870℃ to 930℃ range according to the conventional cooling curve, and the effective residence time of the brick blanks in this range is less than 2 minutes.

[0071] After firing and cooling, the overall glaze surface of the sample showed normal gloss with no obvious dripping. Scanning electron microscopy revealed that the low-melting glass phase was scattered near some open defects, but lacked continuity at the edges of pinholes and shallow pits. Some of the low-melting glass phase had mixed with the main glaze glass phase, and sharp turns still existed at the entrance edges. Cross-sectional measurements of 30 open defects were performed using a three-dimensional white light interferometry profilometer. The entrance edge coverage ranged from 34.2% to 49.5%, with an average of 41.8%; the average radius of curvature of the arc transition edge was 2.1 μm; and the average depth of penetration into the defect was 1.0 μm.

[0072] A simulated bacterial contamination flushing test was conducted according to the method in Example 1. After flushing, the residue at the entrance of some opening defects was reduced compared to Comparative Example 1, but many discontinuous ring-shaped residues were still visible. Statistics from five test areas showed that the contamination residue area accounted for 5.9% to 7.4% of the test area, with an average of 6.6%. After flushing, the samples were placed at 37°C for 24 hours, and then surface samples were taken by wiping. The residual colony count was 9.8 × 10⁻⁶. 3 CFU / cm 2 Up to 1.3×10 4 CFU / cm 2 .

[0073] Based on the microstructure and rinsing results, when low-melting-point glass powder is added alone, if sufficient time is not provided for the formation of the inlet edge during the later stages of firing, the distribution of the low-melting-point glass phase at the entrance of the opening defect is not continuous enough, and the abrupt change at the entrance edge is still quite obvious. The residual contamination area of ​​this group of samples is lower than that of ordinary glossy glaze samples, but significantly higher than that of the sample in Example 1.

[0074] Comparative Example 1 This comparative example prepared ordinary transparent glossy glazed ceramic tiles. The body, glazing method, and firing cycle were basically the same as in Example 1. The glaze slurry used transparent glossy glaze as the base glaze material, which contained feldspar, quartz, kaolin, wollastonite, alumina, and transparent frit, but no low-melting glass powder was added.

[0075] After ball milling, the glaze slurry had a residue of 0.24% on a 325-mesh sieve and a specific gravity of 1.74 g / cm³. 3 The flow rate was 40 seconds. The glaze was applied to the surface of a 600mm x 600mm porcelain tile using a spray method. The wet glaze amount, converted to dry glaze weight, was approximately 482g / m². 2 After glazing, the brick blanks are dried in hot air at 90℃ for 12 minutes, and then sent to a roller kiln for firing. The firing cycle is 64 minutes, the maximum firing temperature is 1161℃, and the high-temperature holding time is about 10 minutes. After the high-temperature stage, the subsequent temperature zone is cooled according to the conventional cooling curve, without setting a holding section near 890℃.

[0076] After firing and cooling, five brick samples from the same batch were examined for glaze surface observation. Scanning electron microscopy revealed that the glaze surface was generally continuous, with pinholes, shallow pits, and a few fine cracks in localized areas. Some pinholes showed abrupt changes at their entry edges, and sharp bends were observed at the edges of the shallow pits. Cross-sectional measurements of 30 open defects were performed using a three-dimensional white light interferometry profilometer. The radius of curvature at the defect entry edges was mainly distributed between 0.4 μm and 1.1 μm, with an average of 0.7 μm; no continuously distributed glassy transition edge along the circumference of the entry was observed.

[0077] The simulated bacterial contamination rinsing test was conducted according to the method in Example 1. 50 μL of simulated bacterial contamination was added to each test point, and after standing at room temperature for 15 min, it was rinsed with water at a flow rate of 0.12 MPa for 15 s. After rinsing, ring-shaped or short arc-shaped residues were visible at the entrances of pinholes and shallow pits. Statistical analysis of the five test areas showed that the contamination residue area accounted for 11.4% to 13.1% of the test area, with an average of 12.2%. After rinsing, the samples were placed at 37°C for 24 h, and surface samples were taken by wiping. The residual colony count was 2.4 × 10⁻⁶. 4 CFU / cm 2 Up to 3.1×10 4 CFU / cm 2 .

[0078] Comparative Example 2 This comparative example prepared ordinary super easy-clean glazed ceramic tiles using porcelain tile blanks of the same specifications as in Example 1. A transparent glossy glaze was used as the base glaze, and a conventional siloxane-based easy-cleaning additive was added to the base glaze at a rate of 0.35% of the dry weight of the glaze. No low-melting-point glass powder was added to the glaze.

[0079] After ball milling, the glaze slurry had a residue of 0.20% on a 325-mesh sieve and a specific gravity of 1.75 g / cm³. 3 The flow rate is 38 seconds. The glaze is applied to the surface of the brick using a spray method, with a dry glaze weight of approximately 488 g / m². 2 After glazing, the brick blanks are dried with hot air at 90℃ for 12 minutes before being fired in a roller kiln. The firing cycle is 65 minutes, the maximum firing temperature is 1160℃, and the high-temperature holding time is about 10 minutes. The post-firing section is cooled according to the production curve of ordinary super easy-clean glaze, and no heat preservation zone is set for the forming of the low-melting glass phase inlet edge.

[0080] After firing and cooling, the sample surface exhibited a relatively uniform gloss, and water droplets spread at a slower rate in the smooth glaze area compared to Comparative Example 1. The surface felt smoother when wiped. Scanning electron microscopy revealed that the smooth glaze area was relatively dense, but abrupt boundaries remained at the entrance edges of pinholes, shallow pits, and localized fine cracks. Three-dimensional white light interferometry was used to measure the cross-sections of 30 opening defects. The radius of curvature at the defect entrance was mainly distributed between 0.6 μm and 1.5 μm, with an average of 1.0 μm. Some opening defects showed signs of glaze leveling improvement around their entrances, but no stable glassy transition edge was formed covering the entrance edge.

[0081] A simulated bacterial contamination rinsing test was conducted according to the method in Example 1. After rinsing, the residue in the smooth glaze area was reduced compared to Comparative Example 1, but obvious discontinuous ring-shaped residues were still present at the edges of pinholes and shallow pits. Statistics from five test areas showed that the contamination residue area accounted for 7.6% to 9.1% of the test area, with an average of 8.4%. After rinsing, the samples were placed at 37°C for 24 hours, and surface samples were taken by wiping. The residual bacterial count was 1.6 × 10⁻⁶. 4 CFU / cm 2 Up to 2.1×10 4 CFU / cm 2 .

[0082] Comparative Example 3 In this comparative example, the same zinc borosilicate low-melting-point glass powder as in Example 1 was added to the base glaze. The low-melting-point glass powder had a D50 particle size of 3.6 μm, a softening temperature of approximately 714 °C, and was added at 2.6% of the dry basis weight of the glaze. The preparation of the body, glaze slurry, glaze application amount, and drying conditions were all the same as in Example 1.

[0083] The glaze slurry was tested through a 325-mesh sieve, and the residue was 0.23%, with a specific gravity of 1.75 g / cm³. 3 The flow rate is 40 seconds. The glaze is applied to the surface of a 600mm x 600mm porcelain tile using a spray method, with a dry glaze weight of approximately 485g / m². 2 After glazing, the brick blanks are dried with hot air at 90℃ for 12 minutes and then sent to a roller kiln for firing. The firing cycle is 64 minutes, the maximum firing temperature is 1162℃, and the high-temperature holding time is about 10 minutes. After the high-temperature stage, the brick blanks are rapidly cooled through the 870℃ to 930℃ range according to the conventional cooling curve, and the effective residence time of the brick blanks in this range is less than 2 minutes.

[0084] After firing and cooling, the overall glaze surface of the sample showed normal gloss with no obvious dripping. Scanning electron microscopy revealed that the low-melting glass phase was scattered near some open defects, but lacked continuity at the edges of pinholes and shallow pits. Some of the low-melting glass phase had mixed with the main glaze glass phase, and sharp turns still existed at the entrance edges. Cross-sectional measurements of 30 open defects were performed using a three-dimensional white light interferometry profilometer. The entrance edge coverage ranged from 34.2% to 49.5%, with an average of 41.8%; the average radius of curvature of the arc transition edge was 2.1 μm; and the average depth of penetration into the defect was 1.0 μm.

[0085] A simulated bacterial contamination flushing test was conducted according to the method in Example 1. After flushing, the residue at the entrance of some opening defects was reduced compared to Comparative Example 1, but many discontinuous ring-shaped residues were still visible. Statistics from five test areas showed that the contamination residue area accounted for 5.9% to 7.4% of the test area, with an average of 6.6%. After flushing, the samples were placed at 37°C for 24 hours, and then surface samples were taken by wiping. The residual colony count was 9.8 × 10⁻⁶. 3 CFU / cm 2 Up to 1.3×10 4 CFU / cm 2 .

[0086] Based on the microstructure and rinsing results, when low-melting-point glass powder is added alone, if sufficient time is not provided for the formation of the inlet edge during the later stages of firing, the distribution of the low-melting-point glass phase at the entrance of the opening defect is not continuous enough, and the abrupt change at the entrance edge is still quite obvious. The residual contamination area of ​​this group of samples is lower than that of ordinary glossy glaze samples, but significantly higher than that of the sample in Example 1.

[0087] Experimental Example 1: Detection of the edge morphology of the entrance to a micro-defect in an opening The entry edge morphology of the micro-defects at the opening was inspected using samples from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. Three brick samples were randomly selected from each group, and one 20mm × 20mm specimen was cut from the central region, the edge region, and the diagonal region of each brick sample. The specimens were ultrasonically cleaned with anhydrous ethanol for 3 minutes, dried at 60°C for 20 minutes, and then observed using a scanning electron microscope and subjected to three-dimensional white light interference profile measurement.

[0088] During scanning electron microscopy observation, five open defects were selected from each sample for recording. These open defects included pinholes, shallow pits, and localized open cracks. For three-dimensional white light interferometry profilometry, the entry edge of each open defect was sectioned, and the radius of curvature of the entry edge, the coverage ratio of the entry edge, and the depth of the transition edge extending into the defect were measured. A total of 45 open defects were measured for each sample group, and the average value was taken.

[0089] Table 3. Detection results of the edge morphology of the opening micro-defect entrance.

[0090] The test results showed that no stable glassy transition edge was observed at the entrance of the opening defects in Comparative Example 1 and Comparative Example 2. The smooth glaze area in Comparative Example 2 was smoother than that in Comparative Example 1, but the entrances of pinholes and shallow pits still retained relatively obvious abrupt edges. In Comparative Example 3, the low-melting glass phase was scattered near the entrances of some opening defects, and the average radius of curvature of the entrance edge increased, but the coverage ratio was low. In the sample of Example 1, a more continuous arc-shaped transition edge was formed at the entrance of the opening defect, and the degree of abrupt change at the entrance edge was significantly reduced.

[0091] From the cross-sectional morphology, the transition edge of the sample in Example 1 is mainly concentrated near the entrance of the opening defect, and a certain depth of indentation is still retained inside the defect. This morphology is different from the cross-section after ordinary leveling or overall filling, and the curvature change at the entrance edge is more concentrated.

[0092] Experimental Example 2: Detection of Bacterial Sewage Film Rinsing Residue Samples from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 were tested for bacterial contamination membrane rinsing residue. Each sample was cut into 100mm × 100mm test pieces. Each test piece was cleaned with neutral detergent, rinsed with deionized water, and wiped with anhydrous ethanol, and then dried at 60°C for 30 minutes.

[0093] The simulated bacterial contamination solution was prepared by mixing an E. coli suspension, a peptone aqueous solution, and edible oil. The concentration of the E. coli suspension was controlled at approximately 1.0 × 10⁻⁶. 6 The concentration of CFU / mL was 0.5% peptone, and the volume fraction of edible oil was 0.2%. During testing, 50 μL of simulated bacterial contamination was dropped onto the surface of each sample, and the sample was allowed to stand at room temperature for 15 min to ensure sufficient contact between the simulated bacterial contamination and the opening defects in the glaze. The sample was then rinsed with a 0.12 MPa water flow for 15 s at a distance of 15 cm. After rinsing, the sample was placed vertically for 2 min, and images were then acquired under a fixed light source and at a fixed shooting distance.

[0094] During image analysis, the test area was divided into a smooth glaze area and an opening defect entry area, and the residual area was calculated separately for each. Five areas were tested for each sample group, and the average value was taken.

[0095] Table 4 Results of residual bacterial film rinsing

[0096] The test results showed that after rinsing, the contamination residue in Comparative Example 1 was mainly concentrated at the entrances of pinholes and shallow pits, with some entrance residues forming continuous rings. In Comparative Example 2, the residue in the smooth glaze area was reduced, but the entrances of opening defects remained the primary residue locations. The residue area in Comparative Example 3 was lower than that in Comparative Examples 1 and 2, indicating that the addition of low-melting-point glass powder had a certain smoothing effect on some entrance edges; however, due to insufficient residence time provided in the later firing stage, the residue at the entrance edges was still quite noticeable. The sample in Example 1 had the lowest contamination residue area after rinsing, and the continuous residue at the entrances of opening defects was significantly reduced.

[0097] After rinsing, the test pieces were placed at 37°C for 24 hours. Samples were then collected by wiping the test area with a sterile cotton swab. The collected samples were serially diluted and then spread for incubation. The incubation results showed that the residual bacterial count on the sample surface in Example 1 was lower than that in the comparative examples. Combined with image observation, the reduced residual bacterial count corresponded to a decrease in contaminant retention at the entrance of the opening defect.

[0098] Experiment Example 3: Stain Retention Test After Scrubbing and Durability To observe the retention of the inlet edge transition structure after repeated cleaning, a scrubbing durability test was conducted on the sample from Example 1 and the samples from Comparative Examples 1 to 3. Each sample was cut into 100mm × 100mm pieces and treated with a damp cloth. The scrubbing cloth was a regular cotton cleaning cloth, the scrubbing load was 9.8N, the scrubbing stroke was 100mm, and the scrubbing frequency was 40 times / min. The scrubbing medium was an aqueous solution containing 0.1% neutral detergent. Samples were taken for testing after 1000 and 3000 scrubbing cycles, respectively.

[0099] After wiping, the sample was rinsed with deionized water and dried at 60°C for 30 min. Subsequently, the residual bacterial contaminant was detected by rinsing using the method in Experiment Example 2, and the radius of curvature of the entrance edge of the opening defect was re-measured using a three-dimensional white light interferometric profilometer.

[0100] Table 5. Results of Stain Retention Test After Washing and Durability

[0101] After 1000 wiping cycles, the arc-shaped transition structure at the entrance of the opening defect in the Example 1 sample remained relatively clear. The average radius of curvature at the entrance edge decreased from 5.4 μm to 5.1 μm, and the average residual contamination area increased from 3.0% to 3.4%. After 3000 wiping cycles, the average radius of curvature at the entrance edge was 4.7 μm, and the average residual contamination area was 4.1%, which was still lower than the residual contamination area in the initial state of each comparative example.

[0102] Comparative Example 2 showed a significant increase in residual contamination area after wiping, mainly manifested in a decrease in the easy-to-clean effect of smooth glaze areas, and an increase in residue at the entrance of opening defects. In Comparative Example 3, the transition structure at some entrance edges was weakened after wiping, and the residual contamination area increased to 8.5% after 3000 wiping cycles. The sample in Example 1 maintained a low residual contamination area after wiping, indicating that the glassy transition structure formed at the entrance edge has a certain degree of durability.

[0103] This experimental example demonstrates that the arcuate transition structure at the entrance edge of the micro-defect opening can maintain its basic morphology after repeated wiping. This structure reduces the adhesion of bacterial contaminant film at the entrance edge, resulting in low contamination residue in the sample both initially and after wiping.

[0104] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0105] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A super easy-to-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer, characterized in that, The invention comprises a blank and a glaze layer disposed on the surface of the blank, characterized in that the glaze layer comprises a main glaze glass phase and a low-melting-point sealing glass phase distributed in the main glaze glass phase; The outer surface of the glaze layer has micro-defects that communicate with the outside world, and the micro-defects have an opening located on the outer surface of the glaze layer; The low-melting-point sealing glass phase forms a rounded edge sealing phase at at least part of the rim, the rounded edge sealing phase covering the acute angle turning point of the rim, and forming an arc-shaped transition edge at the junction of the micro-defect and the outer surface of the glaze layer. The radius of curvature of the arc-shaped transition edge is greater than the radius of curvature of the acute angle turning point of the opening edge where the rounded edge seal phase is not formed, thereby weakening the contact line pinning of the bacterial contaminant film at the micro-defect opening edge.

2. The ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 1, characterized in that, The micro-defects include at least one of pinholes, microcracks, glaze pits, and crystal boundary depressions. The rim is the entrance edge formed by the intersection of the micro-defect and the outer surface of the glaze layer.

3. The ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 1, characterized in that, The rounded edge seal is distributed continuously or intermittently along the circumference of the opening edge; The rounded edge covers 40% to 100% of the total circumferential length of the rim.

4. The ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 1, characterized in that, The radius of curvature of the arc-shaped transition edge is 1.5 μm to 15 μm; The depth of the rounded edge extending into the micro-defect is 0.5 μm to 8 μm.

5. The ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 1, characterized in that, The softening temperature of the low-melting-point sealing glass phase is lower than that of the main glaze glass phase. The difference between the softening temperature of the low-melting-point sealing glass phase and the softening temperature of the main glaze glass phase is 30°C to 160°C.

6. The ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 1, characterized in that, The low-melting-point sealing glass phase includes at least one of borosilicate glass phase, zinc borosilicate glass phase, lithium borosilicate glass phase, and sodium calcium borosilicate glass phase.

7. The ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 1, characterized in that, The low-melting-point sealing glass phase is formed by firing low-melting-point sealing glass powder; The amount of low-melting-point sealing glass powder added is 0.3% to 8% based on the total mass of the glaze used to prepare the glaze layer; The D50 particle size of the low-melting-point sealing glass powder is 0.5 μm to 10 μm.

8. A method for preparing an ultra-easy-clean ceramic tile with a long-lasting antibacterial and self-cleaning glaze layer, based on the ultra-easy-clean ceramic tile with a long-lasting antibacterial and self-cleaning glaze layer as described in any one of claims 1-6, characterized in that, Includes the following steps: Preparation of green body; A glaze layer containing a main glaze and low-melting-point sealing glass powder is applied to the surface of the blank. The green body with the glaze layer applied is fired to form the main glaze glass phase and the low melting point sealing glass powder to form the low melting point sealing glass phase. During the later stages of firing or the initial stages of cooling, the low-melting-point sealing glass phase is kept fluid and enriched at the edges of micro-defects on the outer surface of the glaze layer. After cooling, the low-melting-point sealing glass phase is solidified at the edge of the micro-defect to form a rounded edge sealing phase. The rounded edge sealing phase covers the acute angle turning point of the micro-defect edge and forms an arc-shaped transition edge.

9. The method for preparing an ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 8, characterized in that, The softening temperature of the low-melting-point sealing glass powder is 30°C to 160°C lower than the softening temperature of the main glaze glass phase formed by the main glaze. After the main glaze glass phase has basically taken shape, the low melting sealing glass phase is still in a flowable state and undergoes local backflow to the acute angle turning position of the micro-defect edge under the action of surface tension.

10. The method for preparing an ultra-easy-clean ceramic tile with a long-lasting antibacterial self-cleaning glaze layer according to claim 8, characterized in that, The firing process includes a peak heat preservation section and an edge sealing and forming section; The peak heat preservation section is used to melt the main glaze and form a continuous glaze surface; The temperature of the edge sealing forming section is lower than the temperature of the peak heat preservation section, but higher than the softening temperature of the low melting point edge sealing glass powder. The heat preservation time of the edge sealing forming section is 3 to 30 minutes, so that the low melting edge sealing glass phase preferentially forms a rounded edge sealing phase at the edge of the micro-defect, without requiring complete filling of the internal space of the micro-defect as a necessary condition.